Application of Rain classroom in formal classroom learning in the teaching of offshore engineering environment and loads - Zhu, Hongjun (Computer applications in engineering education, 2021)
A blending approach of mobile learning and formal classroom learning is proposed and applied in the teaching of offshore engineering environment and loads. The Rain classroom developed by Tsinghua University was incorporated into the teacher‐guided classes. A smoother communication, as well as real‐time interaction between teachers and students, was achieved with the aid of mobile learning technology. The participants were juniors from Offshore Oil and Gas Engineering, a subject ranking on the list of world first‐class disciplines. The same examination was issued to both groups after the learning of offshore engineering environment and loads with and without the application of Rain classroom. Furthermore, a survey was conducted on the former group. According to the results, students experienced that the blending learning has a positive attitude toward the reformation of learning mode, and they obtained higher scores in the final examination than the control group. Further extensive studies are required to evaluate the effects of learning intensity, time duration, frequency of teacher–student interaction, and participants from different educational backgrounds.